PRIMARY ENGLISH TEACHERS' UNDERSTANDING AND PRACTICE OF EXISTING CURRICULUM OF ENGLISH EDUCATION IN BANGLADESH: AN EXPLORATORY STUDY - Amin, Ruhul (ANGLISTICUM. Journal of the Association-Institute for English Language and American Studies, 2022)
The study aims at exploring the English teachers' understanding and use of curricular recommendations at primary schools in Bangladesh. Recently, to implement the language teaching policy of communicative approach in English teaching at the primary level, Government of Bangladesh has worked seriously. But with students having little opportunity to use English in their classroom environment and without a sufficient number of qualified English teachers, it is less possible for the students to acquire English language skills as well as to fulfill the purpose of the newest curriculum of NCTB of Bangladesh. Previous researchers have shown that the most of the students of the primary schools are weak in English due to the insufficiency of skilled and trained teachers who are well-known to the latest methodology and approaches of teaching as well as the lack of sufficient materials for teaching in the classroom. The study will also reveal the present condition of English teaching at primary level and investigate the major issues and barriers of teaching as well as reason of not implementing the purpose of latest curriculum by the English teachers’ at the primary level in Bangladesh. Keywords: understanding, curriculum, implement, CLT, practice, materials.